Digital Marketing Activities, Digital Personal Branding, and Purchase Intention for Luxury Makeup: A Mediation Analysis - Ni Putu Anggi Trusiana Maherliza; Desak Made Febri Purnama Sari (Politeknik Siber Cerdika Internasional, 2026)
Background: The rapid development of digital marketing, especially through social media, has changed consumer behavior in seeking information and making purchase decisions. Activities such as influencer marketing engagement, user-generated content (UGC), and viral beauty trends are the main strategies in promoting products, especially in the luxury makeup industry. However, the effectiveness of these activities does not always directly affect purchase intention. Objective: This study examines how influencer marketing engagement, UGC, and viral beauty trends influence purchase intention for luxury makeup products, with digital personal branding as a mediating variable. Methods: This study takes a quantitative approach with a causal associative design. This study's data collection methods include a literature review and questionnaires. This study's analysis utilized a Structural Equation Modeling approach based on Partial Least Squares (SEM-PLS). Results: This study shows that influencer marketing engagement, user-generated content, and viral beauty trends have a positive effect on shaping consumers' digital personal branding on social media. The higher the engagement with influencers, the more content from users, and the stronger the trend develops, the stronger the digital identity of consumers is formed. Digital personal branding has also proven to be the most dominant factor in increasing purchase intention for luxury makeup products. In addition, these three variables affect purchase intention both directly and indirectly, with a stronger indirect effect through digital personal branding. Conclusion: Thus, digital personal branding plays a key role as a mediator that strengthens the relationship between digital marketing activities and consumer purchase intention.